Pengaruh Work Engagement terhadap Work Family Enrichment pada Perawat Ruang ICU - Arya Adithya Ramadhan Hendrofa; Anna Rozana (Bandung Conference Series: Psychology Science, 2023)
Work engagement is a positive state at work that is characterized by vigor, dedication, and absorption (Bakker et al, 2002). Siu et al (2010) revealed that conceptually work engagement can represent an important factor in testing work family enrichment. This research aims to determine the effect of work engagement on work-family enrichment in ICU nurses. The research sample in this study as many as 47 ICU nurses. The research method used is the study causality with quantitative methods. Measuring instruments used in research this is Ultecht Work Engagement (UWES-9) adapted by Kristiana, I. F., & Purwono, U (2019) for measuring tools for work engagement and measuring tools for work-family enrichment from Carlson, et al (2006) which has been adapted by researchers. Technique sampling used the purposive sampling technique. The analytical technique used is multiple regression. The results showed that 61.70% ICU nurses have high work engagement and 65.96% have work families with low enrichment. Multiple regression results show that work engagement positive effect on work-family enrichment (R Square = 0.514). Based on the results of the coefficient of partial determination, shows that the vigor is the aspect of work engagement that has the highest influence on work family enrichment by 25.07%. Work engagement merupakan suatu keadaan positif ketika bekerja yang ditandai oleh vigor, dedication, dan absorption (Bakker et al, 2002). Siu et al (2010) mengungkapkan bahwa secara konseptual work engagement dapat mewakili faktor penting dalam menguji work family enrichment. Penelitian ini bertujuan untuk mengetahui pengaruh work engagement terhadap work family enrichment pada perawat ruang ICU. Sampel penelitian dalam penelitian ini sebanyak 47 perawat ICU. Metode penelitian yang digunakan adalah studi kausalitas dengan metode kuantitatif. Alat ukur yang digunakan dalam penelitian ini adalah Ultecht Work Engagement (UWES-9) hasil adaptasi Kristiana, I. F., & Purwono, U (2019) untuk alat ukur work engagement dan alat ukur work family enrichment dari Carlson, et al (2006) yang telah diadaptasi oleh peneliti. Teknik sampling yang digunakan teknik purposive sampling. Teknik analisis yang digunakan adalah regresi berganda. Hasil penelitian menunjukan bahwa 61,70% perawat ICU memiliki work engagement tinggi dan 65,96% memiliki work family enrichment rendah. Hasil regresi berganda menunjukkan bahwa work engagement berpengaruh positif terhadap work family enrichment sebesar (R Square = 0,514). Berdasarkan hasil koefesien determinasi parsial menunjukan bahwa vigor merupakan aspek work engagement yang memiliki pengaruh paling tinggi terhadap work family enrichment sebesar 25,07%.